Modified Bees Swarm Optimization Algorithm for Association Rules Mining - Mohammed , Rasha A.; Duaimi , Mehdi G.; Sadiq , Ahmed T. (Iraqi Journal of Science, 2022)
Mining association rules is a popular and well-studied method of data mining tasks whose primary aim is the discovers of the correlation among sets of items in the transactional databases. However, generating high- quality association rules in a reasonable time from a given database has been considered as an important and challenging problem, especially with the fast increasing in database's size. Many algorithms for association rules mining have been already proposed with promosing results. In this paper, a new association rules mining algorithm based on Bees Swarm Optimization metaheuristic named Modified Bees Swarm Optimization for Association Rules Mining (MBSO-ARM) algorithm is proposed. Results show that the proposed algorithm can be used as an alternative to the traditional methods.